Physical and Mechanical Properties of Gypsum stone. Engineering and Geological Conditions of Selishchenskoe Deposit of Construction Gypsum - Alvanian, A.K.; Alvanian, K.A. (Vestnik Permskogo universiteta. Serii͡a︡ Geologii͡a, 2019)
The morphology, composition, structure of Selishchenskoe gypsum deposit are analyzed. The qualitative characteristic of the mineral is given. The physical and mechanical properties of the gypsum stone were determined. The engineering and geological conditions of the deposit are estimated.